Testimonies, Liminality Rituals and the Memory of the Self in the Concentration Camps. Issue 2 (3rd May 2016) - Rachmani, Moriya
Abstract : This article is primarily theoretical, presenting preliminary observations on the phenomenon of ritual practice in the Nazi forced labor, concentration and extermination camps as part of the struggle to survive. I shall focus on the way in which ritual observance affected the inmates and their self-perception in various camps. This study is based entirely on various forms of personal testimony. The use of such evidence raises various questions regarding its reliability. Despite the problematic nature and controversy surrounding the testimonies utilized in this study, I regard them as a treasure trove from which it is possible to learn about historical existence from a broader perspective relating to the understanding of the concept of 'testimony'. A large part of my motivation for doing so being the wish to expand the concept of 'testimony, ' I argue that diverse types must be allowed to form the basis of scholarly research. On occasion, testimony regarding rituals takes the form of martyrological or hagiographical stories. I believe that this does not detract from testimony reliability. Orthodox victims and survivors in particular tested or viewed the events through the familiar lens of the 'dark night' of Jewish history, this attitude pervading their writings and testimonies. These thus take the form of the literary genres Jews have traditionally employed down the ages to document their vicissitudes. Hereby, the Nazi atrocities are inserted into familiar categories – pogroms and other violent events in Jewish history. In Lacanian terms, the legendary nature and construction of testimony within narrative conventions forms an attempt to delimit the traumatic real via the symbolic – to demarcate the unspoken 'black hole' through the symbolic order of language. It thus serves as a way of protecting one's self from the outbreak of the 'real' – the essence of the wild demon.